Exploring leadership issues in Papua New Guinea / Murray Prideaux - Prideaux, Murray (Faculty of Business Management, 2008)
The practice of leadership in less developed countries, and Papua New Guinea (PNG) in particular, has not attracted the attention of leadership researchers with the same level of enthusiasm as leadership issues in developed countries. This paper is an exploratory study of the unique leadership issues in the Papua New Guinean (PNG) context. PNG is a diverse Nation of tribal societies largely organised on the basis of kinship and traditional cultural practices. The unique context and challenges of leadership in PNG are not adequately explained by the extant literature. However, 'the bulk of leadership literature is based on a self-limiting set of assumptions, mostly reflecting Western industrialised culture. Almost all the prevailing theories of leadership and almost all of the empirical evidence are rather distinctly American in character' (Littrell, 2002 p:10). Leadership theories based on 'Western' culture are not directly transferable to PNG, whilst significant contextual barriers act to inhibit leadership processes. Leadership issues (Prideaux, 2006) were tested. Respondents reported that the heterogeneous nature of the country, colonial history, diversity, multiple governing systems, vast vicissitude of mutually unintelligible languages, and societies based on patrilineal or matrilineal systems are significant leadership barriers. Results uncover the necessity for an integrative leadership approach contextualised to PNG's unique diversity and complexity, if the country is to fully participate in an increasingly globalised world. Limitations and further research are considered.